Jejunal atresia associated with idiopathic ileal perforation - Das P; Rai Rakesh; Lobo Grover (Wolters Kluwer Medknow Publications, 2008)
Jejunoileal atresia is one of the common causes of neonatal intestinal obstruction. Intestinal perforation with meconium peritonitis in the neonatal period, which carries a high mortality rate, is also common. The association of jejunal atresia with idiopathic ileal perforation is very rare.